2020
DOI: 10.1259/bjr.20190535
|View full text |Cite
|
Sign up to set email alerts
|

Validation of in-house knowledge-based planning model for advance-stage lung cancer patients treated using VMAT radiotherapy

Abstract: Objectives: Radiotherapy plan quality may vary considerably depending on planner’s experience and time constraints. The variability in treatment plans can be assessed by calculating the difference between achieved and the optimal dose distribution. The achieved treatment plans may still be suboptimal if there is further scope to reduce organs-at-risk doses without compromising target coverage and deliverability. This study aims to develop a knowledge-based planning (KBP) model to reduce variability of volumetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The dosimetric improvements for both RP models also came at the cost of an increase in monitor units MU, 489±78 original vs 566±79 for the cardiac-sparing RP (p<0.001) and 569±76 for the clinical RP (p<0.001). This finding is consistent with that of Tahmbe et al who found that for their lung KBP model, re-optimized plans statistically significantly increased plan complexity in both MU and MU/degree 20 . Tahmbe et al further found that this increased complexity did not impact plan deliverability.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The dosimetric improvements for both RP models also came at the cost of an increase in monitor units MU, 489±78 original vs 566±79 for the cardiac-sparing RP (p<0.001) and 569±76 for the clinical RP (p<0.001). This finding is consistent with that of Tahmbe et al who found that for their lung KBP model, re-optimized plans statistically significantly increased plan complexity in both MU and MU/degree 20 . Tahmbe et al further found that this increased complexity did not impact plan deliverability.…”
Section: Discussionsupporting
confidence: 91%
“…KBP has been widely implemented across many different disease sites and allows for a means of partially automating the treatment planning process and reducing variability in plan quality 19 . In the setting of lung irradiation, KBP studies have shown improvements in V5, V20, and mean lung dose 20 . Other KBP models have been used to incorporate more information to the treatment planning process, such as training a model with functional lung volumes to allow for more patient-specific optimization 21 .…”
Section: Introductionmentioning
confidence: 99%
“…In areas where the target and OAR are close to each other, dose distributions with steep dose gradients are often necessary, and the motion of the treatment device tends to be more complicated (20). In recent years, planning devices that can perform treatment planning for VMAT using machine learning have become commercially available, but treatment plans created by machine learning are reported to be more complex in terms of MLC movements than those created manually (21,22). As treatment plans become more complex, MLC positioning accuracy increases in importance (23), and patient-specific verification is more important for the safe delivery of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…5 This is typically achieved through standardization of structures of interest, optimization techniques, and priority values. Specific approaches include, but are not limited to, knowledgebased planning (KBP), [6][7][8] multi-criteria optimization, [9][10][11] and template based planning. 12,13 To this end, the Ethos Adaptive RT platform (Varian Medical Systems, Palo Alto, CA) has been designed with an automated treatment planning system (TPS) that generates plans from userprovided templates.…”
Section: Introductionmentioning
confidence: 99%